Prevalensi infeksi cacing usus soil transmitted helminths pada orang dewasa di Sulawesi Utara - Sorisi, Angle Maria Hasthee; Sapulete, Ivonny Melinda; Pijoh, Victor David (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2019)
Worm disease or helminthiasis, is a disease caused by worms or helminths. Worms that occur are often caused by the Soil Transmitted Helminths (STH) worms, which are worms that are transmitted through the soil. Intestinal helminthiasis is one of the neglected infectious diseases (NIDs) and is still a public health problem in Indonesia. Worm disease is a disease that does not get enough priority in the Health Office program and data on intestinal helminthiasis infection is only limited to the population of school children. The absence of data on helminthiasis in adults in North Sulawesi shows the need for increased awareness about this because not only in children, intestinal helminthiasis can also infect high-risk adults such as people living in slums and poor sanitation, people with immunodeficiency, and people who do a lot of activities with the land. Population density, geographical conditions, and climate also affect intestinal worm transmission. Given the above, it is necessary to conduct research to determine the percentage of STH intestinal helminthiasis infections in adults. This research was conducted in the Clinical Parasitology Laboratory for sample examination. The sample in this study was stool in patients who had stool examination in the Parasitology laboratory. This type of research is analytic descriptive with cross-sectional approach. A total of 40 stool samples, examined using the direct method and examined under a microscope. From the results of laboratory tests, 20 samples (50%) were positively infected by worms. The types of worms found in the sample were Ascaris lumbricoides, Hookworm, Trichuris trichiura, Strongiloides stercoralis. Hookworm infection is the most common type of helminthiasis which is found in 35% of all samples examined followed by Stongiloides stercoralis at 7.5%, Ascaris lumbricoides 5%.